Sasi Pala as a Form of Social Ecology: A Sociological Analysis of Resource Conservation and Community Resilience - Ishaka Lalihun; Clementina. O.M. Rumlus; Afdhal Afdhal (ITScience (Information Technology and Science), 2025)
This study aims to analyze sasi pala as a form of social ecology that contributes to preserving natural resources while strengthening community resilience. Sasi pala, a customary practice in Maluku, regulates nutmeg harvesting to ensure sustainability, maintain ecological balance, and reinforce social cohesion within the community. This research employs in-depth interviews, participant observation, and document analysis using a qualitative approach. The study focuses on the Negeri Seith community, with data analyzed through environmental sociology and community resilience. Findings reveal that sasi pala is a conservation mechanism and a social contract that strengthens local governance and collective responsibility. It prevents overexploitation, facilitates intergenerational knowledge transfer, and ensures economic sustainability through continuous nutmeg production. However, this study is limited to sasi pala communities in Maluku, making its findings less generalizable to other ecological and socio-cultural contexts. Further research should explore sasi practices across different commodities and regions to broaden the understanding of sustainability rooted in indigenous wisdom. This research contributes to environmental sociology, indigenous resource management, and sustainable development discussions. Its insights can inform policymakers and scholars on integrating customary practices into modern conservation strategies. Unlike previous studies focusing primarily on conservation, this study highlights sasi pala as a dynamic socio-ecological institution that not only preserves biodiversity but also strengthens the social resilience of the communities that uphold it.